Hubungan Pekerjaan dan Penghasilan dengan Konsumsi Minuman Keras pada Remaja di Ngemplak Seneng Manisrenggo Klaten Jawa Tengah - Teguh Santoso; Falasifah Ani Yuniarti; Rossida Rossida (LPPM STIKES Guna Bangsa, 2017)
Background: Alcohol consumption in the world at 2015 in the amount of 6.3 litter pure alcohol, the consumer average of age around above 15 years old. Drinking alcohol underage has impact on physical and mental disorders. Purpose: Knowing the relation between employment and income with alcohol consumption in adolescents at Ngemplak Seneng Manisrenggo Klaten Cental Java. Research method: This is a quantitative descriptive study with cross-sectional design. In this used total sampling, 35 subjects participating. Data obtained using question and analyzed by using Chi Square and multiple Regression. Result: Employment (31.4%), income (40.0%), and alcohol consumption (62.9%). From statistical analysis, employment with alcohol consumption shows the p value (0.011) and income with alcohol consumption (0.006). The result from employment and income with alcohol consumption shows the r value (0.819). Conclusion: There is a significant relation between employment and income with alcohol consumption in adolescents.